BASIC AND INTERMEDIATE GNEISSES FROM THE WESTERN PART OF THE SØR RONDANE MOUNTAINS, EAST ANTARCTICA - シライシ, カズユキ; コジマ, サトル; SHIRAISHI, Kazuyuki; KOJIMA, Satoru (National Institute of Polar Research, 1987)
P(論文) This work reports the results of petrography and electron microprobe studies of minerals in basic to intermediate gneisses from the western part of the Sør Rondane Mountains. Mineral paragenesis and electron microprobe data indicate the metamorphic grade in the northern part of the study area is the granulite facies, whereas that of the southern part is the upper amphibolite facies. Estimated P-T conditions of peak metamorphism in the northern part of the area are around 800℃ and 7-8.5kb based on various geothermo-barometries. Widespread retrograde metamorphism caused probably by mylonitization and granite intrusion resulted in the formation of secondary minerals in both the granulite facies and the upper amphibolite facies rocks. departmental bulletin paper